Meningococcal serogroups and surveillance: a systematic review and survey - Peterson, Meagan E; Li, You; Bita, André; Moureau, Annick; Nair, Harish; Kyaw, Moe H; Abad, Raquel; Bailey, Freddie; Garcia, Isabel de la Fuente; Decheva, Antoaneta; Krizova, Pavla; Melillo, Tanya; et al. (Journal of global health, 2019)
Background: Meningococcal disease continues to be a global public health concern due to its epidemic potential, severity, and sequelae. The global epidemiological data on circulating meningococcal serogroups have never been reviewed concurrently with the laboratory capacity for meningococcal surveillance at the national level. We, therefore, aimed to conduct a country-level review of meningococcal surveillance, serogroup distribution, and vaccine use. Methods: We conducted a systematic literature review across six databases to identify studies (published January 1, 2010 to October 16, 2017) and grey literature reporting meningococcal serogroup data for the years 2010-2016. We performed independent random effects meta-analyses for serogroups A, B, C, W, X, Y, and other. We developed and circulated a questionnaire-based survey to surveillance focal points in countries (N = 95) with known regional bacterial meningitis surveillance programs to assess their surveillance capacity and summarized using descriptive methods. Results: We included 173 studies from 59 countries in the final analysis. The distribution of meningococcal serogroups differed markedly between countries and regions. Meningococcal serogroups C and W accounted for substantial proportions of meningococcal disease in most of Africa and Latin America. Serogroup B was the predominant cause of meningococcal disease in many locations in Europe, the Americas, and the Western Pacific. Serogroup Y also caused many cases of meningococcal disease in these regions, particularly in Nordic countries. Survey responses were received from 51 countries. All countries reported the ability to confirm the pathogen in-country, while approximately 30% either relied on reference laboratories for serogrouping (N = 10) or did not serogroup specimens (N = 5). Approximately half of countries did not utilize active laboratory-based surveillance system (N = 22). Nationwide use of a meningococcal vaccine varied, but most countries (N = 36) utilized a meningococcal vaccine at least for certain high-risk population groups, in private care, or during outbreaks. Conclusions: Due to the large geographical variations in circulating meningococcal serogroups, each country should continue to be monitored for changes in major disease-causing serogroups in order to inform vaccine and control policies. Similarly, laboratory capacity should be appropriately scaled up to more accurately understand local epidemiology and disease burden, as well as the impact of vaccination programs.
Keywords: séroskupina; průzkumy a dotazníky; surveillance populace; meningokokové infekce; Meningococcal Vaccines; lidé; celosvětové zdraví; Serogroup; Neisseria meningitidis; Humans; meningokokové vakcíny; Surveys and Questionnaires; Global Health; Meningococcal Infections; Population Surveillance